ANALYSIS OF CRITERIA OF WORKING CONDITION OF SUBSYSTEMS OF LIGHT SIGNAL SYSTEMS OF CIVIL AVIATION AIRPORTS - Шишков, О. Ф.; Дев’яткіна, С. С.; Ванецян, С. Г. (Proceedings of National Aviation University (archive), 2021)
A new scientific approach to determining the criteria for the working condition of the subsystems of all-signal systems of civil aviation aerodromes is proposed. The use of this approach allows to theoretically determine and substantiate the quantitative values of the criteria of operational condition of different subsystems of the light signal system of the aerodrome.